Bank Voles Show More Impulsivity in IntelliCage Learning Tasks than Wood Mice. (1st February 2023) - Jörimann, Marielle; Maliković, Jovana; Wolfer, David P.; Pryce, Christopher R.; Endo, Toshihiro; Benner, Seico; Amrein, Irmgard
Highlights: Medial habenular nucleus size correlates with impulsivity in wild rodents. Bank voles show high impulsivity in the reaction time task. Arc expression in mPFC is rare in bank voles and common in wood mice. Abstract: Impulsivity is a personality trait of healthy individuals, but in extreme forms common in mental disorders. Previous behavioral testing of wild-caught bank voles and wood mice suggested impulsiveness in bank voles. Here, we compared behavioral performance of bank voles and wood mice in tests for response control in the IntelliCage. In the reaction time task, a test similar to the five-choice serial-reaction time task (5CSRTT), bank voles made more premature responses. Impulsivity in the reaction time task was associated with smaller medial habenular nucleus in bank voles. Additional tests revealed reduced behavioral flexibility in the self-paced flexibility task in bank voles, but equal spatial and reversal learning in the chaining/reversal task in both species. Expression of immediate early gene Arc after behavioral testing was low in medial prefrontal cortex, but high in hypothalamic supraoptic and paraventricular nucleus in bank voles. Wood mice showed the opposite pattern. Numbers of Arc-positive cells in the dorsal hippocampus were higher in bank voles than wood mice. Due to continuous behavioral testing (24/7), associations between behavioral performance and Arc were rare. Corticosterone measurements at the end of experiments suggested that IntelliCage testing did not elicit a stress response in these wild rodents. In summary, habenular size differences and altered activation of brain areas after testing might indicate differently balanced activations of cortico-limbic and cortico-hypothalamic circuits in bank voles compared to wood mice. Behavioral performance of bank voles suggest that these rodents could be a natural animal model for investigating impulsive and perseverative behaviors.